Meningkatkan Kemampuan Membaca Anak Melalui Pola Melodi 3 Huruf dan 4 Huruf - Nadila Mokodompit; Sitriah Salim Utina; Sitti Rahmawati Talango (Prodi PGMI STIT Al-Ittihadiyah Labuhanbatu Utara, 2026)
Reading ability is one of the essential skills that should be developed from an early age, as it serves as the foundation for children’s success in subsequent educational stages. However, initial observations conducted in Group B of TK Negeri Pembina Gorontalo Regency revealed that children’s reading skills were still relatively low, particularly in recognizing letters, distinguishing letter sounds, and reading simple three-letter and four-letter words. This study aimed to improve children’s reading ability through the implementation of 3-letter and 4-letter melody patterns. The research employed a Classroom Action Research (CAR) design based on the Kemmis and McTaggart model, consisting of planning, action, observation, and reflection stages carried out in two cycles. The participants were 20 children, comprising 11 boys and 9 girls. Data were collected through observation and interviews and analyzed using descriptive quantitative techniques based on the percentage of developmental achievement. The findings indicated a gradual improvement in children’s reading skills. The average reading achievement increased from 39.06% in the pre-cycle stage to 60.00% in Cycle I and reached 87.50% in Cycle II. These results demonstrate that the use of 3-letter and 4-letter melody patterns is effective in enhancing children’s reading ability, creating an enjoyable learning environment, and increasing their motivation and participation in learning activities.